A 2-fold interpenetrated zinc–organic framework with Lewis basic triazole sites: luminescence sensing of Fe3+ and Cr2O72−, and warm white-light emission by encapsulated Ln3+ ions. Issue 40 (30th September 2022) - Qin, Bowen; Zhang, Xiaoying; Dang, Jiangyan; Yue, Dan; Zhang, Bing; Li, Weidong; Gahungu, Godefroid; Wang, Zhenling; Zhang, Jingping
Abstract : A 2-fold interpenetrated Zn-MOF with Lewis basic triazole sites shows selective luminescence sensing of Fe 3+ and Cr2 O7 2− and tunable white-light emission by encapsulated Ln 3+ ions. Abstract : The design and application of functional metal–organic frameworks are very important and meaningful. Herein, based on a V-shape carboxylic acid ligand, a rigid nitrogen heterocyclic ligand with a triazole group, and Zn(NO3 )2 ·6H2 O, a 3D luminescent Zn-MOF [Zn2 (OBA)2 (L1 )·3DMF·4H2 O] n (compound 1 ; H2 OBA = 4, 4′-oxybis(benzoic acid), L1 = 4-amino-3, 5-bis(4-pyridyl)-1, 2, 4-triazole) with a pillared-layer structure, has been synthesized under solvothermal conditions. Two independent skeletons penetrate each other, forming a 2-fold interpenetrated structure. As an excellent chemical sensor, compound 1 can detect Fe 3+ and Cr2 O7 2− by luminescence quenching with high selectivity and sensitivity. The limits of detection of compound 1 are 0.58 μM for Fe 3+ and 1.37 μM for Cr2 O7 2−, respectively. Meanwhile, compound 1 can serve as a host to encapsulate Eu 3+ /Tb 3+ ions, realizing the tunable luminescence emission of Eu 3+ /Tb 3+ -doped samples. Furthermore, the Eu 3+ /Tb 3+ -co-doped compound 1 obtained by soaking the as-synthesized MOF into Ln 3+ ion solution (total 25 mM; Eu 3+ : Tb 3+ = 2 : 3, molar ratio) exhibits white-light emission with ideal Commission International de I'Eclairage coordinates of (0.32, 0.33), a moderate correlated color temperature value of 6180 K, and an absolute quantum yield of 25.3%. These results indicate that compound 1 has promising applications in ion sensing and white-light emission.